Lieven D’hulst, Chris Van de Poel (eds.), Alles verandert altijd: Perspectieven op literair vertalen. Leuven: Universitaire Pers Leuven, 2019, 278 pp., ISBN 9789462701939 - Tryczyńska, Katarzyna (Werkwinkel, 2019)
Review: Lieven D’hulst, Chris Van de Poel (eds.), Alles verandert altijd: Perspectieven op literair vertalen. Leuven: Universitaire Pers Leuven, 2019, 278 pp., ISBN 9789462701939.